Surveillance for rhabdomyolysis after the consumption of crayfish in Wuhan, China, 2016–2022 - Wu, Yating; Wang, Xiao; Wang, Xiaoye; He, Zhenyu; Wang, Rui; Chen, Zhihan; Wu, Xiaomin (Frontiers in Nutrition, 2024)
To analyze the epidemiological characteristics and etiology of crayfish-related rhabdomyolysis .Methods: Cases of crayfish-related rhabdomyolysis in Wuhan were monitored, and professional training of city's surveillance personnel was conducted. Unified questionnaires were used to collect data.The first case of crayfish-related rhabdomyolysis occurred on July 12, 2016.Subsequently, 423 patients were reported over the next 7 years, with muscle pain, weakness, and chest distress as main symptoms. In total, 64.54% (273/423) of patients were females, and young adults (aged 20-49 years) account for 86.22% (363/423) of patients. The primary clinical presentations were muscle pain, muscle weakness, and chest discomfort. The median incubation time was 6 h. And the number of cases may be related to water levels in Yangzi river. Laboratory tests revealed elevated creatine kinase and myoglobin levels. In total, 95.16% (236/248) of patients had consumed crayfish tail shrimp and 91.53% (227/248) had consumed crayfish liver and pancreas(Female crayfish also contain ovaries). Only 25.00% (62/248) of patients had a history of alcohol consumption. On average, 227 patients consumed 15 (3-50) crayfish, of whom 84.14% (191/227) consumed more than 10 crayfish. All patients had a favorable prognosis.Crayfish-related rhabdomyolysis is a kind of a case or cluster of patients present with severe myalgia or weakness of unknown etiology and mechanism disease in Wuhan, China, 2016-2022. Excessive consumption of crayfish may be a risk factor for the disease. The relationship between the specific parts of crayfish consumed and the onset of the disease is unclear, suggesting further research is needed to identify the relevant risk factors for the disease.